On Square-Closed Lie Ideals and Generalized Homoderivations in Prime Rings - G. Naga Malleswari; S. Sreenivasulu (Integra: Journal of Integrated Mathematics and Computer Science, 2025)
Let M be a square-closed noncentral Lie ideal of a prime ring R with char(R) ≠ 2. An additive mapping G on R is defined as a generalized homoderivation if it satisfies G(στ) = G(σ) h(τ) + G′(σ) y + x h(τ) for all σ and τ in R. This paper focuses on studying generalized homoderivations of prime rings using square-closed Lie ideals that satisfy certain differential identities.